2010
DOI: 10.1016/j.yjmcc.2009.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic approaches for diabetic cardiomyopathy and myocardial fibrosis

Abstract: In diabetes mellitus, alterations in cardiac structure/function in the absence of ischemic heart disease, hypertension or other cardiac pathologies is termed diabetic cardiomyopathy. In the United States, the prevalence of diabetes mellitus continues to rise and the disease currently affects about 8% of the general population. Hence, it is imperative the use of appropriate diagnostic strategies for diabetic cardiomyopathy, which may help correctly identify the disease at early stages and implement suitable cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 66 publications
1
42
0
Order By: Relevance
“…The amino-terminal propeptide of procollagen type III has been reported to rise with insulin resistance in normotensive, nondiabetic obese subjects and may be predictive of early LV dysfunction. 41,42 Support for this concept comes from a recent report by Lopez-Andrès et al, 43 which showed a positive correlation between serum propeptide of procollagen type III and adverse cardiovascular outcomes in subjects with heart failure from the Cardiac Resynchronization in Heart Failure (CARE-HF) trial. Thus, circulating propeptide of procollagen type III might have diagnostic and predictive value as a biomarker of heart failure disease status.…”
Section: Collagen Metabolitesmentioning
confidence: 99%
“…The amino-terminal propeptide of procollagen type III has been reported to rise with insulin resistance in normotensive, nondiabetic obese subjects and may be predictive of early LV dysfunction. 41,42 Support for this concept comes from a recent report by Lopez-Andrès et al, 43 which showed a positive correlation between serum propeptide of procollagen type III and adverse cardiovascular outcomes in subjects with heart failure from the Cardiac Resynchronization in Heart Failure (CARE-HF) trial. Thus, circulating propeptide of procollagen type III might have diagnostic and predictive value as a biomarker of heart failure disease status.…”
Section: Collagen Metabolitesmentioning
confidence: 99%
“…Diabetes is multifactorial and has been associated with various disorders including obesity, dyslipidemia, thrombosis, infarction, hypertension, endothelial dysfunction, and coronary artery disease [25]. However, diastolic and systolic dysfunctions are mainly altered apart from traditional cardiac risks parameters such as hypertension, atherosclerosis, and dyslipidemia [26].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used diagnostic methods are echocardiography and cardiac magnetic resonance imaging (MRI) (8,9). In the early phase of DCP, the pathologic changes can be reversible with strict metabolic control, but in the continuous process the myocardial changes become irreversible and the risk of developing HF increases (10)(11)(12). This review focuses on pathophysiology, diagnosis and management of DCP.…”
Section: Introductionmentioning
confidence: 99%